Scale-up of naringinase production process based on the constant oxygen transfer rate for a novel strain of Bacillus methylotrophicus. Issue 2 (7th February 2017) - Raval, Keyur; Gehlot, Kartik; B. D., Prasanna
ABSTRACT: Naringinase bioprocess based on Bacillus methylotrophicus was successfully scaled up based on constant oxygen transfer rate (OTR) as the scale-up criterion from 5-L bioreactor to 20-L bioreactor. OTR was measured in 5 and 20-L bioreactor under various operating conditions using dynamic method. The operating conditions, where complete dispersion was observed were identified. The highest OTR of 0.035 and 0.04 mMol/L/s was observed in 5 and 20-L bioreactor, respectively. Critical dissolved oxygen concentration of novel isolated strain B. methylotrophicus was found to be 20% of oxygen saturation in optimized medium. The B. methylotrophicus cells grown on sucrose had maximum oxygen uptake rate of 0.14 mMol/L/s in optimized growth medium. The cells produced the maximum naringinase activity of 751 and 778 U/L at 34 hr in 5 and 20-L bioreactors, respectively. The maximum specific growth rate of about 0.178/hr was observed at both the scales of operations. The maximum naringinase yield of 160 and 164 U/g biomass was observed in 5 and 20-L bioreactors, respectively. The growth and production profiles at both scales were similar indicating successful scale-up strategy for B. methylotrophicus culture.